Empowerment of ODGJ (People with Mental Disorders) through Training of Batik Ikat Making in Posyandu Jiwa "Waluyo Jiwo" Bacem Village Ponggok Blitar - Wulandari, Nawang; Nurmawati, Thatit; Setyani, Eka Yulis; Cristiningtyas, Elva Budhy; Arifianti, Khusnul; Saparudin, Agus (Journal of Community Service for Health, 2021)
This community service activity was carried out to increase the productivity of ODGJ (People with Mental Disorders). ODGJ who have experienced improvements and do not have a job, they have not been trusted to work by the community. Besides, below average economic conditions require solutions to overcome them. The purpose of the implementation of this activity was to provide activities or activities that can help improve the economy of ODGJ through empowering ODGJ with training in Batik making. The method used was in the form of training and mentoring for ODGJs to make Batik with several stages, namely the first provision of knowledge and skills to all ODGJ and Mental Health Cadres (as providers of psychological support). The second and third stages were the activities of making Batik Ikat. This activity was carried out for ODGJ who were members of the “Waluyo Jiwo” Jiwa Posyandu in Bacem Ponggok Village, Blitar. The implementation was in February 2020 and followed by 14 ODGJ. The results of this activity indicated that ODGJ were able to follow and carry out activities that had been planned well. Batik activity is one form of occupational therapy for ODGJ that needs to be continued so that ODGJ's independence and entrepreneurial spirit can increase, ODGJ will be more productive